India-Us relations : assessing India’s soft power - Das, Ajaya Kumar (2015)
How do we think about “soft power” theoretically and how do we study it empirically? What is the relationship between economic and military hard power and soft power traditionally understood as based on culture, political values and foreign policy? These questions guide this study of India’s soft power and how it influenced India’s relations with the United States. The puzzling question it aims to answer is why India has been able to exercise its soft power in its relations with the US more effectively in the post-1998 period as compared to the Nehru era (1947-1964).